On Specifying and Visualising Long−Running Empirical Studies. - Wong, P; Gibbons, J (2008)
In this paper we describe a graphical approach for formally specifying temporally-ordered activity routines designed for calendar scheduling. We introduce a workflow model OWorkflow, for constructing specifications of long running empirical studies such as clinical trials in which observations for gathering data are performed at strict specific times. These observations, either manually performed or automated, are often interleaved with scientific procedures, and their descriptions are recorded in a calendar for scheduling and monitoring to ensure each observation is carried out correctly at a specific time. We also describe a bidirectional transformation between OWorkflow and Business Process Modelling Notation (BPMN) diagrams, by which graphical specification, simulation, automation and formalisation are made possible.